NUCLEATION OF CALCIUM CARBONATE ON BACTERIAL NANOGLOBULES - Aloisi G.; Wallman K.; Zuddas P.; Gloter A.; Krüger M.; Guyot F. (My University, 2006)
Nucleation of calcium carbonate on microbial cell material may have been the dominant mode of microbial carbonate formation during most of Earth's history. Current knowledge predicts that nucleation takes place on the cell surface or on extracellular polymeric substances. However, the initial nucleation steps have not been described in detail and the process remains elusive. Here we describe the bacterial nucleation of calcium carbonate at the nanometer scale. In our precipitation experiment with sulfate reducing bacteria (SRB), the bulk of calcium carbonate precipitates on hundreds of individual globules 60-200 nm in diameter. Globules originate from the SRB cell surface but calcify significantly only when released to the culture medium. Similar globules have been observed, albeit at a much larger scale, in other bacterial precipitation experiments and in many natural microbial carbonates, suggesting that the process we describe could be an important step in microbial calcification. © 2006 Geological Society of America.
Keywords: BACTERIA; CARBONATES; ELECTRON ENERGY LOSS SPECTROSCOPY; NUCLEATION; PRECIPITATION EXPERIMENT; TRANSMISSION ELECTRON MICROSCOPY